HUBUNGAN KONDISI EKONOMI ORANG TUA DENGAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 2 KETEGUHAN TBT BANDAR LAMPUNG TAHUN PELAJARAN 2021/2022 - Evi Eviana Wati; Qomario Qomario; Putry Agung (JURNAL ILMU PENDIDIKAN (JURIP), 2022)
The purpose of the study was to determine a significant relationship between the economic conditions of parents and the social studies learning outcomes of fourth grade students of SD Negeri 2 Keteguhan TBT Bandar Lampung. the results of the survey of researchers is that students' social studies learning outcomes are still low. this type of research is quantitative. The design of this study is ex-postfacto correlation and the total population is 27 students, all of which are samples. The results of the study are shown by the results of the product moment correlation test with a correlation coefficient of Tcount 0.621 Trabel 0.381 at the 5% level, which proves that there is a relationship between the economic conditions of parents and learning outcomes.